Social Media Strategies for Enhancing Brand Awareness in a Custom-Made Fashion Business - Jeanne Gloria Laisoka; Inty Nahari (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze how integrated social media marketing strategies implemented by JEGE Official enhance brand awareness in a custom-made fashion business.Research Methodology: This study employed a descriptive qualitative approach using a case study design. Data were collected through non-participant observation of JEGE Official's Instagram, TikTok, Facebook, and WhatsApp Business accounts over a three-month observation period, supported by documentation of digital content and a literature review. Data were analyzed using the interactive qualitative analysis model of Miles, Huberman, and Saldaña.Results: The findings reveal that each platform performs a complementary role. Instagram strengthens visual branding and professional identity, TikTok expands audience reach through short-form video content, Facebook maintains information dissemination and community interaction, while WhatsApp Business facilitates personalized communication that builds customer trust. The integration of these platforms improves brand recognition, recall, credibility, and customer engagement.Conclusions: Integrated social media marketing is an effective strategy for increasing brand awareness in custom-made fashion businesses because it combines visual storytelling, interactive communication, and personalized customer service throughout the customer journey.Limitations: This study is limited to a single case study and relies primarily on qualitative observation without incorporating consumer surveys or social media analytics.Contribution: This study extends digital marketing literature by proposing an integrated multi-platform social media strategy suitable for small creative fashion businesses and provides practical guidance for strengthening brand awareness through coordinated digital communication.